2015
DOI: 10.1016/bs.apha.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Retinoic Acid-Metabolizing Cytochrome P450s, CYP26, in Inflammation and Cancer

Abstract: Vitamin A (retinol) and its active metabolite, all-trans-retinoic acid (atRA), play critical roles in regulating the differentiation, growth and migration of immune cells. Similarly, as critical signaling molecules in the regulation of the cell cycle, retinoids are important in cancers. Concentrations of atRA are tightly regulated in tissues, predominantly by the availability of retinol, synthesis of atRA by ALDH1A enzymes and metabolism and clearance of atRA by CYP26 enzymes. The ALDH1A and CYP26 enzymes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 186 publications
(244 reference statements)
0
55
0
1
Order By: Relevance
“…Several hematopoietic and nonhematopoietic lineages within the gastrointestinal tract, including macrophages, dendritic cells, and lymphocytes T share the capacity to synthesize retinoic acid [78, 79]. A number of studies demonstrated that AtRA has an important modulating role in innate immunity, with the most recent reports showing that RA has a central function in the differentiation of dendritic cells (DCs), the key APCs for activating naive T cells [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Several hematopoietic and nonhematopoietic lineages within the gastrointestinal tract, including macrophages, dendritic cells, and lymphocytes T share the capacity to synthesize retinoic acid [78, 79]. A number of studies demonstrated that AtRA has an important modulating role in innate immunity, with the most recent reports showing that RA has a central function in the differentiation of dendritic cells (DCs), the key APCs for activating naive T cells [80, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data about BP, for example, recurrently provide new insight that should direct therapy, or at least aid diagnosis, and new retinoids are consistently evaluated to improve therapeutic utility, as well use as a component of combination therapy. Alternative approaches to increasing intracellular atRA by inhibiting catabolism also undergo consideration to treat retinoid-related diseases (Stevison et al, 2015). …”
Section: Impact Of Crabp1 Crabp2 and Fabp5 On Human Cancer In Vivomentioning
confidence: 99%
“…However, given that RA is degraded in several local domains in tissues, the systemic concentration of RA in human plasma is not an accurate indicator of overall RA homeostasis and metabolism (Stevison, Jing, Tripathy, & Isoherranen, 2015). Cyp26 enzymes need a membrane environment for activity due to their requirement for P450 reductase, present in the ER membrane (Lutz et al, 2009;Stevison et al, 2015). Hence their activity is often assessed using recombinant proteins in preparations of microsomal fractions isolated from tissues and cell lines.…”
Section: Kin Et I Cs Of R a De Gr Ad A Tionmentioning
confidence: 99%